The superiority and perspectives in single-atom site and multi-atom site catalysts for energy conversion - Qizheng An; Chenyu Yang; Yanzhi Xu; Feifan Yu; Jingjing Jiang; Chen Gong; Baojie Li; Jing Zhang; Qinghua Liu (APL Materials, 2022)
Atomically dispersed metal catalysts have been a research hotspot in the field of nanocatalysis due to their unique advantages in recent years. The isolated single or few atoms can be anchored on supports via chemical bonding or space confinement to maximize atom utilization efficiency, reducing the use of metal resources while displaying distinguished catalytic performance. This perspective presents the latest advances in single-atom site catalysts (SACs) and multi-atom site catalysts (MACs), highlights their superiority, and discusses the current limitations as well as the outlooks facing their future development.